2016
DOI: 10.3390/v8030079
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Intra-Type Variants of Oncogenic Human Papillomaviruses by Next-Generation Deep Sequencing of the E6/E7 Region

Abstract: Different human papillomavirus (HPV) types are characterized by differences in tissue tropism and ability to promote cell proliferation and transformation. In addition, clinical and experimental studies have shown that some genetic variants/lineages of high-risk HPV (HR-HPV) types are characterized by increased oncogenic activity and probability to induce cancer. In this study, we designed and validated a new method based on multiplex PCR-deep sequencing of the E6/E7 region of HR-HPV types to characterize HPV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 58 publications
1
15
0
1
Order By: Relevance
“…Our previous study demonstrated enhanced tumourigenesis by the full HPV16 genome with AAE6 [31], while another study presented altered gene expression by the AA variant [89]. Work by other groups have studied the downstream pathways in the AA variant [90, 91], and have utilized high-throughput techniques to investigate genetic variation within HPV16 [39, 40, 92], but this is the first study investigating the downstream pathways affected by the HPV16 variants in an organotypic epithelial model using next-generation sequencing. We hypothesized two scenarios that can be associated with these findings and analyzed in our present study: i) the global gene expression profile within AAE6-infected epithelium would differ significantly from that of EPE6 and ii) significant gene expression differences in the host due not only to the actions of the viral oncogenes E6 and E7, but also as a result of integration [56].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study demonstrated enhanced tumourigenesis by the full HPV16 genome with AAE6 [31], while another study presented altered gene expression by the AA variant [89]. Work by other groups have studied the downstream pathways in the AA variant [90, 91], and have utilized high-throughput techniques to investigate genetic variation within HPV16 [39, 40, 92], but this is the first study investigating the downstream pathways affected by the HPV16 variants in an organotypic epithelial model using next-generation sequencing. We hypothesized two scenarios that can be associated with these findings and analyzed in our present study: i) the global gene expression profile within AAE6-infected epithelium would differ significantly from that of EPE6 and ii) significant gene expression differences in the host due not only to the actions of the viral oncogenes E6 and E7, but also as a result of integration [56].…”
Section: Resultsmentioning
confidence: 99%
“…1). Modern deep sequencing techniques have been used to study HPV [3539], but only recently in the context of intratypic variants [40], and not using an organotypic epithelial model with full viral variant genomes. Instead, our complete approach allowed a comparison of these variants with regards to their integration capacity and subsequent transcriptional consequences in close to in vivo conditions, resulting in viral integration and a molecular signature of host chromosomal instability for AAE6 only.…”
Section: Introductionmentioning
confidence: 99%
“…High-risk (HR) HPV persistent infections have been shown to be key drivers of cervical cancer initiation and progression, but different HR-HPV types may have different oncogenic activities [37]. HPV-16/18 are most carcinogenic among the different HR-HPV types.…”
Section: Discussionmentioning
confidence: 99%
“…Generalmente, el IFNA tiene su máximo efecto entre la cuarta y la octava semana; no obstante, en algunos pacientes después de 12 a 16 semanas los papilomas no han desaparecido, por lo que se requiere una segunda aplicación, si el paciente tiene más de diez papilomas (29). El IFNA 2b tiene pocos efectos secundarios y se utiliza en 106 UI/ml de dosis cuatro veces al día, hasta la resolución completa de la lesión (14-20 semanas) (41). El IFNA puede administrarse como monoterapia o como un adyuvante después de la cirugía (28,40,42).…”
Section: Interferón (Ifn) Aunclassified